2014
DOI: 10.1111/ppc.12095
|View full text |Cite
|
Sign up to set email alerts
|

Resourcefulness in African American and Caucasian American Caregivers of Persons With Dementia: Associations With Perceived Burden, Depression, Anxiety, Positive Cognitions, and Psychological Well-Being

Abstract: Purpose Providing care to persons with dementia can have negative effects on caregivers' physical and psychological well‐being. This secondary analysis explored relationships among perceived burden, depression, anxiety, resourcefulness, and psychological well‐being in 28 African American (AA) and 45 Caucasian American (CA) caregivers of persons with dementia. Design and Methods Descriptive, cross‐sectional design was used to examine the hypothesized relationships in a sample of 73 caregivers. Findings CAs repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 55 publications
3
23
2
Order By: Relevance
“…When compared with African‐American carers, Caucasian‐American carers reported greater levels of burden, anxiety, depression, and hostility. African‐American carers reported higher levels of resourcefulness, positive cognitions, and psychological well‐being than their Caucasian counterparts. Gaugler and colleagues reported that Caucasian carers were more likely to indicate low resilience than non‐Caucasian carers.…”
Section: Social and Cultural Characteristicsmentioning
confidence: 93%
See 2 more Smart Citations
“…When compared with African‐American carers, Caucasian‐American carers reported greater levels of burden, anxiety, depression, and hostility. African‐American carers reported higher levels of resourcefulness, positive cognitions, and psychological well‐being than their Caucasian counterparts. Gaugler and colleagues reported that Caucasian carers were more likely to indicate low resilience than non‐Caucasian carers.…”
Section: Social and Cultural Characteristicsmentioning
confidence: 93%
“…The review highlighted evidence suggesting a relationship between carer outcomes and ethnicity and culture. Three articles explored the impact of ethnicity and culture on family caregiving for PWD. Two studies examined the ethnicity of carers .…”
Section: Social and Cultural Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the problems, psychological disorders suffered by caregivers include anxiety and depression . The health they perceive is very low, and most report being dissatisfied or very dissatisfied with their health in general affecting the quality of life even in those caregivers who begin to take care of minor stages of the disease …”
Section: Introductionmentioning
confidence: 99%
“…7 The existing evidence shows that higher rates of anxiety and depression on the family caregivers of people with dementia are likely to be found when compared with caregivers of people without this health problem. [8][9][10] Evidence also shows that despite the caregivers' exhaustion and physical burden, they constantly delay seeking help and neglect their own health. 11 The level of family burden caused by dementia, even in the early stages, is recognized as a public health problem.…”
Section: Introductionmentioning
confidence: 99%